Penerapan Model Pembelajaran Problem Based Learning Dengan Pendekatan Saintifik Untuk Meningkatkan Pemahaman Konsep Matematika (PTK Pembelajaran Matematika Kelas X AK 1 SMK Negeri 1 Banyudono Tahun Ajaran 2014/2015) - Aji, Tsaqibu J.N.S.A, Rita P. Khotimah, S.Si., M.Sc, M. Noor Kholid, S.Pd., M.Pd (2015)
Tsaqibu Jabal Nur Shaffati Aji/ A410112011. The Application of Problem Based Learning Model With The Scientific Approach to Improve The Understanding of Mathematical Concepts (CAR of Mathematics Class X AK 1 in SMK Negeri 1 Banyudono Academic Year 2014/2015). Thesis. Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta. June, 2015. The purpose of this research is to describe the improvement of student's understanding of mathematical concepts by applying Problem Based Learning model with scientifict approach. This research is a Classroom Action Research (CAR) collaborative. The subject that receive the action is grade X AK 1 of SMK Negeri 1 Banyudono academic year 2014/2015. The number of students of grade X AK 1 are 36 students. The data collection techniques are observation, field notes, test and documentation. The technique of data analysis is plots methode. Based on the research analysis it can be concluded that the application of Problem Based Learning Model with scientifict approach can improve student's understanding of mathematical concepts on trigonometry subject. It can be seen from the increase in the precentage of indicators understanding of mathematical concepts, namely 1) the ability of students to use the formula correctly before the action as much as 27.78% increase to 75%; 2) the ability of students to give examples as much as 16.67% increase to 69.44%; 3) the ability of students to use mathematical symbols as much as 11.11% increase to 77.78%; 4) the ability of students to change the story problems into mathematical models increased as much as 13.89% to 83.33%. The conclusion of this study is that the application of learning models Problem Based Learning (PBL) with a scientific approach to enhance understanding of mathematical concepts class X AK 1 SMK 1 Banyudono academic year 2014/2015. Keywords: conceptual understanding, problem based learning, scientific